Server consolidation using OpenVZ: performance evaluation - Ahmed, Mohiuddin; Zahda, Showayb; Abbas, Majed (Institute of Electrical and Electronics Engineers ( IEEE ), 2008)
Virtualization is abstracting computer resources. It is the ability to run multiple operating systems simultaneously on a single physical machine. In this paper we evaluate the performance of the operating system level virtualization software (OpenVZ). The evaluation will be based on Web hosting, in other words, we evaluate the performance of Web servers on two different machines (dubbed as Baru and Lama) and we observe the behavior of OpenVZ and its scalability for Web servers on different architectures (32 bits and 64 bits). The study evaluates the CPU, Memory and Throughputs under different loading conditions.